Health Promotion and Social Support of Jordanian Adolescents During COVID-19 Pandemic - Eman Hourani; Sawsan Hammad; Maha Albqoor; Abeer Shaheen (Jordan University of Science and Technology, 2023)
Abstract Background: During the COVID 19 pandemic, new polices were established to decrease the transmission of infection. These changes in polices might have an impact on health promoting activities and social support among adolescents. Objective: The purpose of this study was to describe the levels of health promoting activities and the impact of social support among adolescents. Method: Descriptive cross-sectional design was applied to collect data from 298 Jordanian adolescents. Results: Females reported a significantly higher mean score than males in total AHPS, peer support, health responsibility, life appreciation, and stress management. Males’ adolescents scored a significantly higher in physical activity average. The developmental stage of adolescents had an impact on the health promoting activities. Conclusion: Differences in health promoting activities based on adolescents’ gender is an area that need more investigation. Because of the importance of social support, family and social support must be improved. Implication for Nursing: The differences in performing health promoting activities based on adolescents’ gender are areas that need more attention. fostering social support from family and peers is crucial. It is mandatory to activate the role of the community health nurse as soon as possible. Keywords: Adolescents health; health promotion, peer support, family support